Pemanfaatan OPAC dalam Mendukung Penelusuran Informasi Pemustaka di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Santikha, Annisa Dwi; Rahmah, Elva; Marlini, Marlini (TSAQOFAH, 2026)
The use of the Online Public Access Catalog (OPAC) is a key component in supporting users’ information retrieval in libraries, yet in practice OPAC has not been optimally utilised, particularly in regional public libraries that serve users with diverse educational backgrounds and levels of information literacy, potentially hindering the effectiveness of information retrieval. This study aimed to analyse the use of OPAC in supporting users’ information searching at the Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat. The research employed a qualitative method with a descriptive design, using in-depth interviews with library users and direct observation of OPAC use within the library, with informants selected through purposive sampling based on their experience in utilising OPAC. Data were analysed through the stages of data reduction, data display, and conclusion drawing using a thematic approach. The findings show that OPAC has been used as an initial tool for information searching to help users identify the titles, authors, availability, and locations of collections, with search features based on title and author name being the most frequently used because they are considered easy and practical. Nevertheless, several challenges remain, including users’ limited understanding of OPAC features, a lack of usage guidelines, unstable system performance, and discrepancies between OPAC records and the actual collections on the shelves. The study concludes that while OPAC use has supported users’ information searching, it has not yet reached an optimal level; the implications underscore the need to improve OPAC service quality through regular updating of collection data, enhancement of system performance, and strengthening of users’ information literacy so that OPAC can be utilised more effectively in public libraries.